2020
DOI: 10.1039/d0ta05927g
|View full text |Cite
|
Sign up to set email alerts
|

Rational valence modulation of bimetallic carbide assisted by defect engineering to enhance polysulfide conversion for lithium–sulfur batteries

Abstract: The reasonable design of metal compound electrocatalysts is proved to be a good way to accelerate the sluggish conversion kinetics of polysulfides for high performance lithium-sulfur (Li-S) batteries. Since metal...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 55 publications
0
20
0
Order By: Relevance
“…Defects in catalysts play an importance role in tuning the intrinsic electronic structure to polar property. [ 151–158 ] The active defect‐rich catalysts are beneficial to modulate the catalytic activity for the LiPS conversion. Lin et al.…”
Section: Superior Highly Active Defect‐rich Catalysts In Sulfur Cathodementioning
confidence: 99%
See 1 more Smart Citation
“…Defects in catalysts play an importance role in tuning the intrinsic electronic structure to polar property. [ 151–158 ] The active defect‐rich catalysts are beneficial to modulate the catalytic activity for the LiPS conversion. Lin et al.…”
Section: Superior Highly Active Defect‐rich Catalysts In Sulfur Cathodementioning
confidence: 99%
“…Defects in catalysts play an importance role in tuning the intrinsic electronic structure to polar property. [151][152][153][154][155][156][157][158] The active defect-rich catalysts are beneficial to modulate the catalytic activity for the LiPS conversion. Lin et al [148] initially put forward the ideas of using anionic-defected catalyst of MoS 2-x to enhance LiPS conversion kinetics so as to decrease their accumulation in the sulfur cathode and shuttling, which obviously improves the battery performance.…”
Section: Defect-rich Nanocatalysts In Accelerating Kinetics Of Srrs A...mentioning
confidence: 99%
“…Recently, metal phosphides, nitrides and carbides ( e.g. , NbN, 329 CoP, 330 Ni 3 ZnC 0.7 , 331 and Mo 2 C 332 ) have been used for the design of functional separators due to their metallic conductivity. Wang et al demonstrated that MoP 2 nanoparticles had high catalytic activity for PS, and thus the Li–S battery with the MoP 2 /CNT-coated separator exhibited a high reversible capacity and cycling stability.…”
Section: Functions Of Mpm Separatorsmentioning
confidence: 99%
“…158 Since metal ions usually serve as the active sites to interact with polysuldes, optimizing their electronic and valence states is vital to enhance the catalytic activity, especially in sulfur redox reactions involving multiple electrons. 159 In addition, the metal atomdoping strategy shows metallic characteristics and even superconductivity, 160 which is very benecial to facilitate the redox reaction kinetics and increase the sulfur utilization efficiency for Li-S batteries. The single metal atom doped in carbon matrix is widely known as single-atom materials, which will be discussed separately in this review.…”
Section: Heteroatom Doping Strategymentioning
confidence: 99%